Teacher as Philosopher? Patočka's Philosophical View on Education - Stojka, Róbert (Ruch Filozoficzny, 2023)
Jan Patočka was one of the first philosophers in Czechoslovakia who, in addition to other areas of philosophy, also dealt with the philosophy of education. These ideas of his, concerned with the philosophical view of education, are still relevant today. The starting point of this study is, above all, Patočka's basic thesis, which states that a teacher who forms his/her pupils in a fundamental way must him/herself have a certain attitude towards the world and his/her life clarified, which means creating his/her own life schedule that gives his/her life meaning. For Patočka, this meaning is the result of a daily struggle to continually acquire it. It is the formation of this world view, which the teacher then transmits to his/her pupils, that is, according to Patočka, the purpose of education as such. It thus prepares the teacher for the responsible exercise of his/her profession so that he/she can perform it adequately as a humanly valuable personality. This is a crucial moment in which philosophy can go beyond a purely theoretical approach to the world towards a practical application in the educational process.